A pilot study comparing custom contoured and planar support surfaces for pressure ulcer risk over the heels for night time postural management using interface pressure mapping and discomfort scores. Issue 3 (August 2017) - Hosking, J.
Abstract: Purpose: Custom contouring techniques are effective for reducing pressure ulcer risk in wheelchair seating. These techniques may assist the management of pressure ulcer risk during sleep for night time postural management. Objectives: To investigate the effectiveness of custom contoured night time postural management components against planar support surfaces for pressure ulcer risk measures over the heels. Method: Supine posture was captured from five healthy participants using vacuum consolidation and 3-dimensional laser scanning. Custom contoured abduction wedges were carved from polyurethane and chipped foams. Pressure mapping and the visual analog scale were used to evaluate the effectiveness of the contoured foams in reducing pressure and discomfort under the posterior heel against standard planar support surfaces. Results: Custom contoured shapes significantly reduced interface pressures (p < 0.05) and discomfort scores (p < 0.05) when compared to planar support surfaces. Polyurethane foam was the most effective material but it did not differ significantly from chipped foam. Linear regression revealed a significant relationship between the Peak Pressure Index and discomfort scores (r = 0.997, p = 0.003). Conclusions: The findings of this pilot study suggested that custom contoured shapes were more effective than planar surfaces at reducing pressure ulcer risk surrogate measures over the posterior heels with polyurethane foam being the most effective material investigated. It is recommended that Evazote foam should not be used as a support surface material for night time postural management. Highlights: Pressure ulcer risk for night time postural management was investigated. Custom contoured surfaces performed more favourably than planar support surfaces. Different materials in night time postural management design is evaluated. Polyurethane foam was most effective in reducing pressure ulcer risk measures.